2021
DOI: 10.1055/s-0041-1740188
|View full text |Cite
|
Sign up to set email alerts
|

Development, Implementation, and User Evaluation of COVID-19 Dashboard in a Third-Level Hospital in Iran

Abstract: Introduction The implementation of a dashboard enables managers to make informed and evidence-based decisions through data visualization and graphical presentation of information. This study aimed to design and implement a COVID-19 management dashboard in a third-level hospital in Mashhad, Iran. Materials and Methods This descriptive developmental applied study was conducted in the second half of 2020 in three stages, using user-centered design methodology in four phases: (1) specification of the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…8,29 Dashboard tools are increasingly used to support clinical decisions. 14,25 Tools that display data across a time spectrum during hospitalization can be helpful in providing a larger understanding of the patient's interrelated clinical needs. 30 The proof of concept design to better understand MHAC explored in this study suggested clinicians value dashboards that are visually easy to interpret.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,29 Dashboard tools are increasingly used to support clinical decisions. 14,25 Tools that display data across a time spectrum during hospitalization can be helpful in providing a larger understanding of the patient's interrelated clinical needs. 30 The proof of concept design to better understand MHAC explored in this study suggested clinicians value dashboards that are visually easy to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…12 Goals of clinical decision support tools are to increase patient safety, quality, and efficiency of care, patient engagement, care coordination, interprofessional communication, and improve clinician efficiency. [12][13][14] The most commonly cited frustrations reported by clinicians with EHR use are poor workflow designs, navigation to multiple screens, and alert fatigue. 12,13,15 In principle, dashboards provide data visualization to facilitate clinician decisions.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The "COVID-19 Panel", widely viewed since 2020, is based on this tool and allowed managers agility in combating the disease and optimizing resources. 9,10 A disadvantage of Power BI is the difficulty of programming the databases. However, training, even virtual training, can solve this issue.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…(4,5). In such circumstances, the optimal management of resources and workforce is one of the most critical responsibilities of hospital managers, who also need access to up-to-date evidence about patients and available resources (6)(7)(8)(9). This is the case especially in EDs where information systems are needed to support communication and care coordination (10).…”
Section: Introductionmentioning
confidence: 99%